ACUTE MACULAR NEURORETINOPATHY AFTER SARS-COV-2 VACCINATION. Issue Volume 16:Issues 1(2022) (January 2022) - Patel, Samir N.; Yonekawa, Yoshihiro
Abstract : Purpose: To present the rare case of a patient who developed acute macular neuroretinopathy (AMN) after administration of a single-dose adenovector coronavirus vaccine. Methods: Retrospective chart review. Results: A 26-year-old woman presented with paracentral scotomas in both eyes that acutely developed 2 days after administration of a single-dose adenovector SARS-CoV-2 vaccine (Johnson & Johnson, New Brunswick, NJ). She had previously received the seasonal influenza immunization without any symptoms and denied having any recent history of viral illnesses. On examination, optical coherence tomography showed parafoveal hyperreflective bands in the outer retina of both eyes without retinal thickening and near-infrared reflectance showed wedge-shaped parafoveal lesions pointing to the fovea, both classic findings in acute macular neuroretinopathy. Discussion: This report highlights the development of acute macular neuroretinopathy after a SARS-CoV-2 vaccination in an otherwise healthy female patient. A single case cannot establish cause and effect, and millions of COVID-19 vaccines have been administered safely at the time of writing. However, this may be a rare association, and clinicians can consider inquiring about recent vaccination history in patients presenting with acute macular neuroretinopathy. Abstract : This case report highlights the development of acute macular neuropathy after administration of a single-dose adenovector coronavirus vaccine in an otherwise healthy female patient.